Digital Islamic Business Ethics: Video Unboxing as a Khiyar mechanism in Online Buying and Selling Transactions - Andrian Harmoko; Diana Ambarwati (Jurnal Internasional Ekonomi Islam, 2022)
This article describes unboxing video content as a khiyar mechanism in online transactions. The sale and purchase transaction is declared invalid if one of the parties feels compelled and disadvantaged due to product defects. The method used in this article is a field research study with a phenomemological approach. The findings of this study are that video unboxing becomes the mechanism of choice for buyers to Khiyar or the choice to continue or cancel the transaction made. Buyers who upload unboxing videos showing product defects are given the opportunity to cancel the transaction or exchange it for a new product. This mechanism arises because sellers and buyers do not meet directly in the online transaction process. Video unboxing is done as a form of awareness and responsibility (responsibility) in muamalah as a form of ethics in business. The unboxing video will ultimately give pleasure to both the seller and the buyer as a condition for the fulfillment of blessings in the transaction